Avetianella longoi sp. n. (Hymenoptera Encyrtidae) egg parasitoid of Phoracantha semipunctata F. (Coleoptera Cerambycidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Avetianella longoi sp. n. (Hymenoptera Encyrtidae) is described from Italy as an effective egg parasitoid of Phoracantha semipunctata F. (Coleoptera Cerambycidae), a serious pest of Eucalyptus spp. all over their growing areas.
Keywords: Hymenoptera Encyrtidae; Avetianella longoi sp. n.; egg parasitoid; Phoracantha semipunctata; Eucalyptus spp.; Italy